Communication Strategy for Deliberalization of Islamic Thought at UNIDA Gontor - Rifki Aulia (Sahafa Journal of Islamic Communication, 2024)
Liberalism, when viewed from its development, has two main streams that mutually use the term liberal. Classical liberalism or economic liberalism emphasizes individual freedom in carrying out activities in the economic field, and social liberalism, emphasizes the state's role in defending individual rights, usually formed as anti-discrimination laws. In addition to the trend of liberalization which emphasizes economic, political, and social rights, liberalism is also found in the field of religious thought. Indeed, liberalism in Western civilization's social and political fields has slowly separated religion from social and political affairs. Religion has no place in social and political interests. Concepts such as pluralism, multiculturalism, feminism, gender equality, democratization, humanism, freedom, and human rights are several layers of elements in the liberalization movement. Even theses and dissertations in Islamic universities are written to seek Islamic justification for these concepts. To stem this massive liberalization movement, researchers take the example of preventing the liberalization of Islamic thought in Islamic tertiary institutions, namely at the University of Darussalam (UNIDA) Gontor. This type of research is qualitative, with in-depth interview data collection techniques, and data analysis techniques namely triangulation of data sources (results of interviews and previous research). The result of this research is that UNIDA Gontor uses a curriculum based on the Islamization of Science. In addition, Islamization activities are also carried out through weekly student discussions guided by mentors, bi-weekly studies for lecturers and staff, scientific papers written by students and lecturers, and community service activities.